Novel tools to study cell-ECM interactions, cell adhesion dynamics and migration - Dibus, Michal (Elsevier, 2025)
Integrin-mediated cell adhesion is essential for cell migration, mechanotransduction and tissue integrity. In vivo, these processes are regulated by complex physicochemical signals from the extracellular matrix (ECM). These nuanced cues, including molecular composition, rigidity and topology, call for sophisticated systems to faithfully explore cell behaviour. Here, we discuss recent methodological advances in cell-ECM adhesion research and compile a toolbox of techniques that we expect to shape this field in future. We outline methodological breakthroughs facilitating the transition from rigid 2D substrates to more complex and dynamic 3D systems, as well as advances in super-resolution imaging for an in-depth understanding of adhesion nanostructure. Selected methods are exemplified with relevant biological findings to underscore their applicability in cell adhesion research. We expect this new “toolbox” of methods will allow for a closer approximation of in vitro experimental setups to in vivo conditions, providing deeper insights into physiological and pathophysiological processes associated with cell-ECM adhesion.